USING ONE MINUTE LIFE STORY FOR TEACHING SPEAKING TO SENIOR HIGH SCHOOL STUDENTS - Mela Ismi; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2018)
This article discusses about the use of One Minute Life Story in teaching speaking to senior high school students. Speaking is one of the four main skills in language that should be mastered by the students especially in English. To support and increase students’ speaking ability, teacher can use One Minute Life Story as an activity in the classroom. One minute life story is a part storytelling activity but it has the difference which is limited by the time. In this paper, the way of using it may be different because English is a foreign language in Indonesia. So that, one minute time is extended and become five minutes, by using One Minute Life Story it is expected that students can practice and increase their speaking ability with a different way.